Tribute to César Vallejo in Spain - Flores Heredia, Gladys (2018)
The Spanish critical tradition has given to the studies on the work of César Vallejo remarkable contributions that are scattered in books, prologues, notes, articles, several university theses and the elaboration of editions of the different collections of poems of the bard from Santiago de Chile. The realization of the III International Congress Vallejo Siempre 2018 in Salamanca, Spain, is a propitious occasion to reflect on the state of the Vallejo question in the Spanish academic community, as well as to exchange knowledge about the research being carried out in different parts of the world. This homage to Vallejo in Spain is the continuation of the Vallejo biennials initiated and institutionalized in the city of Lima in the framework of the International Congress Vallejo Siempre 2014, and that had continuity in the city of Montevideo, with the International Congress Vallejo Siempre 2016. And just as the Vallejo quixotism of Francisco Távara Córdova (Peru) and the heraldic lyricism of Andrés Echevarría (Uruguay) were exemplary in those contests, this Spanish version of the congress is entirely due to the medullar humanity of Gonzalo Santonja Gómez-Agero, the maker.